Craniofacial Fibrous Dysplasia: Retrospective Study on the Relationship Between the Tumor Volume Changes and the Circulating Serum Calcitonin and Serum Alkaline Phosphatase. Issue 3 (March 2017) - Hussein, Mohammed Ahmed; Yun, In Sik; Kim, Bo Ok; Kim, Yong Oock
Abstract : Background: The purpose of this study was to determine the usefulness of serum alkaline phosphatase (ALP) and calcitonin in the follow-up of tumor volume changes in patients with craniofacial fibrous dysplasia. Methods: Twenty patients with isolated craniofacial fibrous dysplasia were included, who met our criteria for long-term follow-up. Three-dimensional computed tomography scans were obtained, and tumor segmentation was performed. The tumor volume was measured preoperatively, immediate postoperative and during long-term follow-up. Serum ALP and calcitonin levels were obtained at the same times to assess their correlation with tumor volumes. Results: Preoperative calcitonin levels were correlated with the presence of tumor ( P = 0.0442), whereas ALP levels were not ( P = 0.1125). There were no significant associations between tumor volume and ALP or calcitonin levels in the preoperative or postoperative periods. During long-term follow-up, serum ALP was significantly associated with tumor recurrence ( P = 0.0096), but serum calcitonin was not ( P = 0.4760). However, serum levels of ALP did not reflect the tumor volume changes. Conclusions: Serum ALP may be useful as a laboratory test for follow-up of patients with isolated craniofacial fibrous dysplasia. However, it cannot represent the tumor's volume changes and 3-dimensional computed tomography scans with tumor volume measurement are mandatory for detecting significant volume changes during follow-up. Investigation of the serum calcitonin in the preoperative period is also recommended on a large scale because it was related to the presence of the tumor.